Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/ibi.12689
|View full text |Cite
|
Sign up to set email alerts
|

Central–periphery gradient of individual quality within a colony of Black‐headed Gulls

Abstract: Central nesting sites within avian colonies are often more profitable in terms of fitness, as they can offer better protection against predators compared with colony edges. Thus, central sites are expected to attract high‐quality individuals, which should produce a clear central–periphery gradient in the phenotypic quality of nesting individuals and reproductive output within colonies. The aim of this study was to assess spatial patterns of individual quality within a colony of a common larid, the Black‐headed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…While studying black-headed gulls in rural areas (Kusowo), we noted that almost all individuals infected with Campylobacter (97.1%) located their nests at the periphery of the breeding colony. This corresponds with results of our earlier studies in the same colony, where we found evidence for higher physiological condition of birds breeding in the colony centre (Indykiewicz et al 2018b). Thus, it seems likely that central pairs may also be more resistant to pathogens than peripheral low-quality pairs.…”
Section: Discussionsupporting
confidence: 93%
“…While studying black-headed gulls in rural areas (Kusowo), we noted that almost all individuals infected with Campylobacter (97.1%) located their nests at the periphery of the breeding colony. This corresponds with results of our earlier studies in the same colony, where we found evidence for higher physiological condition of birds breeding in the colony centre (Indykiewicz et al 2018b). Thus, it seems likely that central pairs may also be more resistant to pathogens than peripheral low-quality pairs.…”
Section: Discussionsupporting
confidence: 93%
“…After removing outliers, the H/L ratio distribution remained right skewed (skewness = 1.37) and was, thus, log transformed to improve normality. The repeatability of the H/L ratio was relatively high (R = 0.81, P < 0.001), as assessed through independent measurements of the same smears prepared for 25 individuals captured in previous seasons (Indykiewicz et al 2019b). Although leucocyte profiles (and possibly some other physiological traits, e.g.…”
Section: Physiological Stressmentioning
confidence: 99%
“…The elevated social stress is recognized as a possible cost of avian coloniality [ 14 ]. Consistently with this hypothesis, it has been shown in black-headed gull that birds nesting in central colony area (areas of higher nest density) are affected by stronger social stress, as indicated by elevated heterophile/lymphocyte (H/L) ratios [ 36 ]. In general, changes in H/L ratios are induced by exposure to external stressor (e.g.…”
Section: Discussionmentioning
confidence: 80%
“…In general, birds nesting in more attractive, high-density areas are expected to be of higher phenotypic and genetic quality [ 13 , 49 ], which can have a positive effect on the quality of offspring. In fact, central areas of black headed gull colonies were previously shown to be occupied by adult birds with higher blood haemoglobin concentration and higher size-corrected body mass, indicating their better individual quality in terms of body condition [ 36 ]. The artificial reduction of colony size in herring gull Larus argentatus resulted in improvement of body condition of the breeders [ 50 ], which shows constraint inflicted by competition with conspecifics.…”
Section: Discussionmentioning
confidence: 99%